EVALUATION OF THE MECHANICAL PROPERTIES OF HYBRID COMPOSITE MATERIALS UNDER TENSION - Mikosianchyk, Oksana; Shevchenko, Oleh; Dubovyk, Vladyslav; Mnatsakanov, Stepan; Golembiyevskyy, Grygoriy; Fedorchuk, Svitlana (Problems of Friction and Wear, 2026)
The study investigates the behavior of interlayer hybrid polymer composite materials (HPC) based on carbon and glass fabric under static tension, considering the specific features of their deformation. Hybrid composites based on carbon and glass fabric with different layer stacking schemes by vacuum forming are studied. The results show that the deformation of HPC under tension in the longitudinal direction is complex and is accompanied by the occurrence of various processes that dominate at certain stages of elongation of the studied sample under load. Deformation diagrams for HPC samples were obtained, revealing a nonlinear deformation response in the strain range of 0.25–0.8%. This nonlinearity is attributed to increasing stress concentrations in the polymer matrix, intensified plastic deformation, matrix cracking, interfacial delamination, and load transfer to the reinforcing fibers. Two points of rupture of the samples during uniaxial tension were determined: the first rupture is caused by brittle fracture of carbon fibers, the second rupture is associated with the destruction of glass fibers by the pulling mechanism. The formation of an 8-layer HPC with two outer layers based on structural roving glass fabric and two layers of unidirectional carbon fabric parallel to the applied load and four inner layers of satin weave glass fabric provides a maximum tensile strength of 660.7 MPa (first rupture), a tensile strength of 275.5 MPa (second rupture) with a maximum relative elongation of the composite of 1.88%. The results of the research are relevant in the development of interlayer HPCs by combining carbon and glass fibers in order to achieve high strength of the HPC through carbon fiber and improved energy absorption processes due to plastic deformation of glass fibers in the structure of the hybrid composite.